Analisis Semiotika Kumpulan Puisi Memo Kemanusiaan Karya Akhmad Sekhu Sebagai Bahan Ajar Bahasa dan Sastra Indonesia di SMA - Rosyanti, Rosyanti (Jurnal Artikula, 2024)
This research aims to analyze the meanings within the poetry collection “Memo Kemanusiaan” by Akhmad Sekhu using Roland Barthes' semiotic approach. The focus of the analysis is on the denotative, connotative, and mythological meanings present in these poems, as well as how these findings can be applied as teaching materials for the Indonesian language and literature at the high school level. Barthes’ semiotic approach is employed to uncover the hidden meanings behind the signs and symbols used in the poetry. The selected poems encompass themes such as the COVID-19 pandemic, love for the homeland, and social life. The results of the study indicate that the poems in “Memo Kemanusiaan” contain numerous connotative and mythological meanings that illustrate various values of life, struggle, and humanity. For instance, in the poem titled “Kartini Surat-suratmu Masih Tetap Tersirat,” the denotative meaning portrays the struggle of an individual symbolized by “Kartini,” a woman who fought for independence through her dedication. In contrast, the connotative meaning of this poem represents a symbol of struggle and sacrifice by a woman for the independence of the nation and for the freedom of all women. The mythological meaning embedded in this poem conveys the notion that fighting for independence is the right and duty of all humanity. The research also finds that these poems can serve as effective teaching materials for analyzing meaning in language and literature classes, aligning with the independent curriculum. Semiotic analysis assists students in understanding the implied meanings in poetry and developing critical thinking skills regarding literary texts. This study contributes to the development of teaching methods for the Indonesian language and literature in high schools and highlights the importance of semiotic analysis in gaining a deeper understanding of literary works.